Sustainable management of insect pests and diseases in rice in rainfed low land ecosystem: A case study - Mohapatra, S D; Rath, P C; Jena, M (Indian Journal of Plant Protection, 2020)
On-farm IPM trial on rice was conducted in rainfed low land ecosystem in the Pipili block of Puri district in Odisha. The pest scenario and management strategies were evaluated under two regimes viz., 1. Farmers’ practice (FP): (a) Direct seeding (b) Non-specifc pest monitoring both in the nursery and main felds (c) Application of pesticides after seeing the damage 2. IPM treatments: (a) Row planting (20 × 15 cm) (b) Field monitoring through routine feld survey (b) Cartap hydrochloride 4G @ 25 kg/ha applied at 15 DAT (c) Need based application of foliar spray of chlorantraniliprole 18.5 SC @ 30 g.a.i./ha and (d) Need based application of fungicide. In case of IPM, 8.2% dead heart ( DH), 4.5% white ear head (WEH) due to stem borer, 5.8% silver shoot due to gall midge, 6.8% sheath blight infections, 1.6% balls due to false smut were recorded; whereas in case of FP, 12.5% DH, 7.2% WEH, 10.6% sheath blight, 2.8% false smut balls were found. In IPM plots, predator population was more (6.2 sweep-1) compared to FP plots (5.4 sweep-1) which includes spider, damselﬂy, dragon ﬂy, mirid bugs whereas parasitoid population was 4.5 sweep-1 in IPM and 4.1 sweep-1 in FP plots. The grain and straw yields in IPM treatments were 5.4, 10.4t/ha, respectively compared to 4.3 and 9.5t/ha in FP treatment. BC ratio in IPM was 1.84 whereas in FP it was 1.69. Farmers were trained for the identifcation of insect pests and their natural enemies to decide the timing of pest management practices.